KERAPATAN TUMPUKAN DAN KERAPATAN PEMADATAN TUMPUKAN DEDAK PADI DARI BERBAGAI KABUPATEN YANG DICAMPUR DENGAN SEKAM PADI - A. Y., ALFARESI; HERNAMAN, I.; SAEFULHADJAR, D. (Majalah Ilmiah Peternakan, 2023)
Rice bran mixed with rice husk often occurs in the feed industry, as a result of scarcity of rice bran as animal feed. The aim of the study was to study the heap density and compaction density of rice bran obtained from various districts mixed with rice husk. The study was conducted experimentally using a 2-way classification design consis- ting of 4 treatments of rice bran and rice husk mixtures and 5 districts. Data were analyzed by means of variance followed by Duncan’s multiple range test. The results showed that the mixture of rice bran and rice husk in various districts showed significant differences (P<0.05). Adulteration of rice bran by rice husk can be detected by adding 60% rice husk to bulk density and 40% to compact bulk density. The value of compact bulk density is faster in detecting the adulteration of rice bran with rice husk compared to the value of bulk density. The conclusion of this study is that at the level of 40% addition of rice husk, adulteration of rice bran can be determined by measuring the compact bulk density.